Anthropology of Music: Contributions of the Academic Production in Costa Rica - Álvarez López, Jessica Dixiana (2025)
Introduction: The Anthropology of Music focuses on understanding the impact and function of music in society, exploring its production, transmission, and impact. Objective: This paper seeks to present some of the contributions made to the study of music from an anthropological perspective in Costa Rica. Methods: A bibliographic research of academic texts written in the field of Anthropology that focused on the study of music was carried out. From this review, the texts were categorized, and points in common between the research were identified in order to deepen some methodological and thematic approaches made from these texts. Results: In total, 27 academic texts were analyzed, with an equal production between sexes and a peak of publications between 2000 and 2019. The papers focused on their contributions to the topic of musical genres (ska, reggae, rock, metal, punk, etc.), the low participation of women, and their concentration in the Huetar Atlantic and Central Region of the country. Conclusions: The diversity of thematic as well as methodological approaches (especially from ethnography) evidenced that music has not only an artistic but also a social and cultural impact, which allows the duplication of particular and symbolic dynamics.